2018
DOI: 10.1039/c8sm00226f
|View full text |Cite
|
Sign up to set email alerts
|

Efficient simulation method for nano-patterned charged surfaces in an electrolyte solution

Abstract: We present a method to efficiently simulate nano-patterned charged surfaces inside an electrolyte solution. Simulations are performed in the grand canonical ensemble and are used to calculate the force between surfaces with various charge patterns. The electric field produced by the surfaces is calculated analytically and is used as an external potential. To treat the long range Coulomb interaction between the ions we use a modified 3d Ewald summation method. The force between the surfaces is found to depend s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 40 publications
(43 reference statements)
0
16
0
Order By: Relevance
“…As stated above, full cDFT framework is general enough to include explicit hard-sphere solvent and non-electrostatic mean field solvent-ion interactions that produce a more complete model, which better mimics the experimental system than either the primitive model or previous MD simulations (see Supplementary Discussion for details). However, this complexity renders the cDFT model closer to a full molecular simulation that is difficult to validate-either with more traditional molecular simulations or by performing a self-consistent check of the theory through a full simulation of the charged hard-sphere system in a hard-sphere solvent interacting via a patterned dielectric nanoparticle 59,60 . Moreover, whether a neutral hardsphere is a meaningful representation of an associating fluid (like methanol) is an open question 61 as is the form of the nonelectrostatic solvent interaction.…”
Section: Resultsmentioning
confidence: 99%
“…As stated above, full cDFT framework is general enough to include explicit hard-sphere solvent and non-electrostatic mean field solvent-ion interactions that produce a more complete model, which better mimics the experimental system than either the primitive model or previous MD simulations (see Supplementary Discussion for details). However, this complexity renders the cDFT model closer to a full molecular simulation that is difficult to validate-either with more traditional molecular simulations or by performing a self-consistent check of the theory through a full simulation of the charged hard-sphere system in a hard-sphere solvent interacting via a patterned dielectric nanoparticle 59,60 . Moreover, whether a neutral hardsphere is a meaningful representation of an associating fluid (like methanol) is an open question 61 as is the form of the nonelectrostatic solvent interaction.…”
Section: Resultsmentioning
confidence: 99%
“…In the present work, we have studied the adsorption of poly-electrolytes to nano-patterned charged surfaces using a recent method for simulation of these kinds of systems 30 . It is shown that all polyelectrolytes are adsorbed to domains with opposite charge and concentrated at the center of the domains where there is higher charge density.…”
Section: Discussionmentioning
confidence: 99%
“…Since the system has slab geometry we use a corrected 3D Ewald summation 31 . The total potential energy of the system composed of N hard sphere particles of charge q i located at r r r i can be written as follows 21,30 : where…”
Section: The Model and Simulation Detailsmentioning
confidence: 99%
See 1 more Smart Citation
“…30 Furthermore, the periodic pattern of the surface becomes imprinted on the electrolyte solution through the renormalization of the Debye length, which controls the interactions between the charged species and The Journal of Chemical Physics ARTICLE scitation.org/journal/jcp the nanopatterned wall. 31,32 Lack of continuous symmetry and presence of strong ionic interactions between charged patches and the monomers of polyampholyte makes the problem very difficult to study using analytical methods. [33][34][35][36] On the other hand, computer simulations provide a direct way to explore both the adsorption and the structure of the polyampholytes near a nanopatterned surface.…”
Section: Introductionmentioning
confidence: 99%